Should I Stay or Should I Go? Managing Sponsor Relations through Athlete Transgressions. Issue 2 (3rd April 2018) - Roberts, Samantha; Burton, Nicholas
ABSTRACT: This research seeks to examine the impact of athlete transgressions on endorsement decision-making and dissolution within the context of relationship marketing, within the context of trust as a determinant of relationship development and dissolution. The present study's findings suggest that, when faced with such trigger events, key to the sponsor decision-making process is the risk tolerance and awareness of the sponsor, and the appreciation of risk and vulnerability embedded within the relationship. This acceptance of risk, and the corresponding trust and commitment fostered, represents an important component of relationship management in endorsement contracts. Correspondingly, a model of relationship restoration or dissolution is proposed, conceptualizing the decision-making process for endorsees. This research thus begins to address the managerial implications of transgression for endorsees, in order to better understand the antecedents underpinning the decision-making process of the sponsor in response to a case of sporting transgression.